2016
DOI: 10.1021/acs.jmedchem.6b00860
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Dopamine D3 Receptor (D3R) Antagonists and Partial Agonists Based on Eticlopride and the D3R Crystal Structure: New Leads for Opioid Dependence Treatment

Abstract: The recent and precipitous increase in opioid analgesic abuse and overdose has inspired investigation of the dopamine D3 receptor (D3R) as a target for therapeutic intervention. Metabolic instability or predicted toxicity has precluded successful translation of previously reported D3R-selective antagonists to clinical use for cocaine abuse. Herein, we report a series of novel and D3R crystal structure-guided 4-phenylpiperazines with exceptionally high D3R affinities and/or selectivities with varying efficacies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(160 citation statements)
references
References 56 publications
6
153
1
Order By: Relevance
“…Our results suggest that the robust attenuation of morphine-induced locomotion previously observed with nonselective D2-like receptor antagonism is primarily attributable to blockade of the D2R subtype. Moreover, our finding that pretreatment with the selective D3R antagonist PG01037 produces a significant, albeit weaker, attenuation of morphine-induced locomotion is in accord with a number of recent studies that also demonstrate modest reductions of the locomotor-activating effects of opioids following pretreatment with other highly-selective D3R antagonists (Kumar et al 2016;Lv et al 2019;You et al 2017). Based on these prior findings and our present results with PG01037 and L-741,626, we conclude that D3R antagonism and D2R antagonism exert qualitatively similar reductions of morphine-induced hyperlocomotion, however a pharmacological shift away from D3R selectivity towards either nonselective antagonism or selective D2R antagonism renders this modulation far more robust.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results suggest that the robust attenuation of morphine-induced locomotion previously observed with nonselective D2-like receptor antagonism is primarily attributable to blockade of the D2R subtype. Moreover, our finding that pretreatment with the selective D3R antagonist PG01037 produces a significant, albeit weaker, attenuation of morphine-induced locomotion is in accord with a number of recent studies that also demonstrate modest reductions of the locomotor-activating effects of opioids following pretreatment with other highly-selective D3R antagonists (Kumar et al 2016;Lv et al 2019;You et al 2017). Based on these prior findings and our present results with PG01037 and L-741,626, we conclude that D3R antagonism and D2R antagonism exert qualitatively similar reductions of morphine-induced hyperlocomotion, however a pharmacological shift away from D3R selectivity towards either nonselective antagonism or selective D2R antagonism renders this modulation far more robust.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, D3R antagonism may "mask" the overt appearance of sensitization during the induction phase due to its capacity to attenuate morphine-induced hyperactivity, but the development of the underlying sensitization can be "unmasked" and observed when morphine is tested in the absence of D3R antagonism. It is noteworthy that this hypothesis is in conflict with a recent report that pretreatment with the highly-selective D3R antagonist VK4-116 attenuated the induction of oxycodone-induced locomotor sensitization (Kumar et al 2016) as assessed by a challenge test with oxycodone alone. However, some key procedural differences may underlie these discrepant findings including the use of different opioids (morphine vs. oxycodone), use of different D3R antagonists (PG01037 vs. VK4-116), and imposition of 7 days vs. 2 days between the final induction session and the expression test.…”
Section: Discussionmentioning
confidence: 64%
“…29 Three D 2 -like receptor antagonists were then chosen to disclose the possible contribution of D4R and D2SR in the effect of pramipexole: L745-870, with selective high affinity for D4R [30][31][32] ; raclopride, with high affinity for D2R and D3R but low affinity for D4R 31,32 ; and VK4-116, a recently introduced compound with selective high affinity for D3R. 25 The in vitro recovery of these compounds through the optogenetic-microdialysis probe at the same flow rate used in the in vivo experiments (1 ml/min), as analyzed by HPLC (see Materials and Methods), was 12.0 6 0.7%, 8.2 6 0.2%, and 20.6 6 0.6% for L745-870, raclopride, and VK4-116, respectively. These figures provide an approximation to the effective extracellular concentration of drugs administered through the microdialysis probe (reverse dialysis).…”
Section: Effect Of D 2 -Like Receptor Antagonists On Pramipexole-medimentioning
confidence: 99%
“…33 The concentration of the D 2 -like receptor antagonists in the perfusion media (10 lM) should therefore yield extracellular concentrations around the probe of around 1 lM or lower, which would be insufficient for L745-870 to bind significantly to D2R or D3R, for raclopride to bind to D4R, and for VK4-116 to bind to D2R or D4R. 25,[30][31][32] Coperfusion with 10 lM of L745-870 or raclopride, but not VK4-116, significantly counteracted the effect of pramipexole (1 lM), and the optogenetic stimulation could still increase glutamate release both in controls (at 100Hz) and in animals with BID (at 60Hz; Fig 3A, B). The results therefore imply a participation of both D4R and D2SR, but not D3R, in the effect of pramipexole.…”
Section: Effect Of D 2 -Like Receptor Antagonists On Pramipexole-medimentioning
confidence: 99%
“…It was found that the drugs affecting the dopaminergic system can also influence the effect of opioid agonists on cognitive functions in animal models. [7][8][9][10][11][12][13][14] These results are expected to be useful for further understanding of the tolerance and dependence phenomena in opioids addiction.…”
Section: Introductionmentioning
confidence: 92%